Further data on the reliability of the mentalization imbalances scale and of the modes of mentalization scale - Giulia Gagliardini; Laura Gatti; Antonello Colli (Research in Psychotherapy, 2020)
The aim of this study was to provide data on the Inter-Rater Reliability (IRR) and the test-retest reliability of the Mentalization Imbalances Scale (MIS) and the Modes of Mentalization Scale (MMS) in two different studies. Three junior raters and two senior raters assessed blindly 15 session transcripts of psychotherapy of five patients, using both the MIS and the MMS. The same 15 sessions were rated after the junior raters completed a training at the use of the scales and after on month from the end of the training to assess testretest reliability. Four therapists used the MIS and the MMS to provide different ratings of 22 patients undergoing a psychotherapy in different settings. Intraclass Correlation Coefficient (ICC) values ranged from sufficient to good and increased after the training. Test re-test reliability was sufficient for both scales (Study 1). ICC values ranged from sufficient to good, and were globally higher than the ones found in the first study sample (Study 2). Our results provide support to the inter-rater reliability of the MIS and the MMS.